please help me solve this partial-fraction decomposition!

12x-57/(x-3)(x-10)

2 answers

let
A/(x-3) + B(x-10) = (12x-57)/((x-3)(x-10))

then
A(x-10) + B(x-3)/((x-3)(x-10)) = (12x-57)/((x-3)(x-10) )

or
A(x-10) + B(x-3) = 12x - 57
let x = 10
B(7) = 63 ----> B = 9

let x = 3
A(-7) = -21 ----> A = 3

so:
(12x-57)/((x-10)(x-3)) = 3/(x-3) + 9/(x-10)
thank you! :)
Similar Questions
    1. answers icon 3 answers
  1. (7x^2-16)/(x^2-2x)solve by using partial fraction decomposition. i cant figure out how to do this because after i split up the
    1. answers icon 3 answers
    1. answers icon 2 answers
    1. answers icon 3 answers
more similar questions